Association of periprocedural perfusion non-improvement with recurrent stroke after endovascular treatment for Intracranial Atherosclerotic Stenosis. (December 2022) - Yan, Long; Hou, Zhikai; Fu, Weilun; Yu, Ying; Cui, Rongrong; Miao, Zhongrong; Lou, Xin; Ma, Ning
Background: Predictors of recurrent stroke after endovascular treatment for symptomatic intracranial atherosclerotic stenosis (ICAS) remain uncertain. Objectives: Among baseline characteristics, lesion features, and cerebral perfusion changes, we try to explore which factors are associated with the risk of recurrent stroke in symptomatic ICAS after endovascular treatment. Design: Consecutive patients with symptomatic ICAS of 70–99% receiving endovascular treatment were enrolled. All patients underwent whole-brain computer tomography perfusion (CTP) within 3 days before and 3 days after the endovascular treatment. Baseline characteristics, lesion features, and cerebral perfusion changes were collected. Methods: Cerebral perfusion changes were evaluated with RAPID software and calculated as preprocedural cerebral blood flow (CBF) < 30%, time to maximum of the residue function (Tmax) > 6 s, and Tmax > 4 s volumes minus postprocedural. Cerebral perfusion changes were divided into periprocedural perfusion improvement (>0 ml) and non-improvement (⩽ 0 ml). Recurrent stroke within 180 days was collected. The Cox proportional hazards analysis analyses were performed to evaluate factors associated with recurrent stroke. Results: From March 2021 to December 2021, 107 patients with symptomatic ICAS were enrolled. Of the 107 enrolled patients, 30 (28.0%) patients underwent balloon angioplasty alone and 77 patients (72.0%) underwent stenting. The perioperative complications occurred in three patients. Among CBF < 30%, Tmax > 6 s, and Tmax > 4 s volumes, Tmax > 4 s volume was available to evaluate cerebral perfusion changes. Periprocedural perfusion improvement was found in 77 patients (72.0%) and non-improvement in 30 patients (28.0%). Nine patients (8.4%) suffered from recurrent stroke in 180-day follow-up. In Cox proportional hazards analysis adjusted for age and sex, perfusion non-improvement was associated with recurrent stroke [hazards ratio (HR): 4.472; 95% CI: 1.069–18.718; p  = 0.040]. Conclusion: In patients with symptomatic ICAS treated with endovascular treatment, recurrent stroke may be related to periprocedural cerebral perfusion non-improvement. Registration: http://www.chictr.org.cn . Unique identifier: ChiCTR2100052925.